The Effect Of Perceived Benefits In Formatting Male Online Shoppers' Attitude - Yokie Radnan Kristiyono; Erlyn Ribkah Roring; Ian Nurpatria Suryawan (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
This study addresses (1) whether convenience is the multidimensional construct in perceived benefits. (2) whether the price is the multidimensional construct in perceived benefits. (3) whether the product variety is the multidimensional construct in perceived benefits. (4) whether the perceived benefit influences the attitude towards online shopping. (5) whether the attitude towards online shopping influences the online purchase intention. The data used in this study are collected from a total of 240 respondents who are male and users of the 10 most widely used e-commerce in Indonesia. The study reveals that perceived benefits are a multidimensional construct that is reflected in three dimensions, namely convenience, price, and variety of products. Second, perceived benefits have a positive relationship to attitudes toward online shopping among men. Third, attitude toward online shopping has a positive relationship to online purchase intention. E-commerce companies' perceived benefits can have a positive influence on consumers' online attitudes.